1999
DOI: 10.1002/hep.510300430
|View full text |Cite
|
Sign up to set email alerts
|

Long-term therapy and retreatment of hepatorenal syndrome type 1 with ornipressin and dopamine

Abstract: Peripheral vasodilation is considered an important factor in the pathophysiology of the hepatorenal syndrome (HRS). Therefore, the aim of this study was to evaluate the therapeutic potential of the vasoconstrictor ornipressin plus dopamine in the treatment of the most severe form of HRS, namely HRS type 1. Seven cirrhotic patients (creatinine clearance 15 ؎ 1 mL/min, UNaV 7 ؎ 2 mmol/24 h) with HRS type 1 were included in the study after normalization of central venous pressure with intravenous albumin and low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1
8

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(113 citation statements)
references
References 34 publications
4
100
1
8
Order By: Relevance
“…The rate of adverse events leading to withdrawal in this study (5%) is consistent with findings in the literature and is reported to be lower with terlipressin as compared with vasopressin and other vasopressin analogues. [37][38][39] In summary, terlipressin plus albumin is superior to placebo for reversal of type 1 HRS and produces a significant decrease in SCr compared with placebo and albumin. Administration of albumin by itself also had a modest salutary effect and reversed HRS in 13% of cases.…”
Section: Discussionmentioning
confidence: 93%
“…The rate of adverse events leading to withdrawal in this study (5%) is consistent with findings in the literature and is reported to be lower with terlipressin as compared with vasopressin and other vasopressin analogues. [37][38][39] In summary, terlipressin plus albumin is superior to placebo for reversal of type 1 HRS and produces a significant decrease in SCr compared with placebo and albumin. Administration of albumin by itself also had a modest salutary effect and reversed HRS in 13% of cases.…”
Section: Discussionmentioning
confidence: 93%
“…until GFR had increased to above 40 mL/min or until adverse events prevented further treatment. 48 Renal function improved in four patients after 5-27 days. In two patients, treatment was discontinued because renal function did not improve.…”
Section: Ornipressinmentioning
confidence: 92%
“…105 Lack of a natriuretic response after improvement of renal function may be related to severe liver dysfunction in these patients, as onset of natriuresis has been shown to be related to a threshold of liver function. [106][107][108][109] When terlipressin was combined with either intravenous albumin 110 or a renal vasodilator such as low-dose dopamine, 10 the result was even more encouraging, with suppression of the renin-angiotensin activity and normalization of serum creatinine in a number of patients without serious ischemic side effects. These observations further support the concept that both splanchnic and systemic arterial vasodilatation with effective arterial underfilling, resulting in increased circulating levels of vasoconstrictors, play pathogenetic roles in the development of HRS.…”
Section: Vasopressin Analoguesmentioning
confidence: 99%
“…In HRS, systemic vasoconstrictors such as metaraminol improved urinary sodium excretion but not renal function, 111 whereas norepinephrine 112 or dopamine 10 were ineffective. Oral administration of an ␣-adrenergic agonist, midodrine, improved systemic and renal hemodynamics in nonazotemic cirrhotic patients but had no effect in patients with HRS.…”
Section: ␣-Adrenergic Agonistsmentioning
confidence: 99%
See 1 more Smart Citation